2009
DOI: 10.4014/jmb.0809.555
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Spermidine Transport System in a Cyanobacterium,Synechocystis sp. PCC 6803

Abstract: The transport of spermidine into a cyanobacterium, Synechocystis sp. PCC 6803, was characterized by measuring the uptake of 14 C-spermidine. Spermidine transport was shown to be saturable with an apparent affinity constant (K m ) value of 67 µM and a maximal velocity (V max ) value of 0.45 nmol/min/mg protein. Spermidine uptake was pHdependent with the pH optimum being 8.0. The competition experiment showed strong inhibition of spermidine uptake by putrescine and spermine, whereas amino acids were hardly inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Polyamines are a group of nitrogen (amine) containing compounds that received recently considerable attention owing to its possible role in abiotic stress resistance [ 48 ]. Studies on polyamine transport in cyanobacteria have been scarce, but the implication of polyamine transport to protect Synechosystis against salt stress has been reported [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polyamines are a group of nitrogen (amine) containing compounds that received recently considerable attention owing to its possible role in abiotic stress resistance [ 48 ]. Studies on polyamine transport in cyanobacteria have been scarce, but the implication of polyamine transport to protect Synechosystis against salt stress has been reported [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…An exogenous addition of spermidine enhanced the cell growth of Synechocystis sp. PCC 6803 in the presence of 0.5 M NaCl [44]. As shown in Figure 2, spermidine concentrations increased to 2.0 and 13.8 µmol g −1 DW at 0.5 M NaCl and 1 M NaCl after 1 h. The spermidine concentration remained high at 1 M NaCl (above 10 µmol g −1 DW) but decreased gradually at 0.5 M NaCl (Figure 2).…”
Section: Tricarboxylic Acid Cycle Urea Cycle and Polyamine Synthesismentioning
confidence: 81%
“…It has been reported that Synechocystis 6803 can take up spermidine (31). We tested the effect of exogenous spermidine on the RACLT of sll0873::Km r .…”
Section: Resultsmentioning
confidence: 99%
“…Homospermidine synthase is not found, but deoxyhypusine synthase may transform putrescine into homospermidine, in certain groups of cyanobacteria (28). Like other bacteria, cyanobacteria can take up polyamines from the environment (29)(30)(31)(32) and may secrete polyamines (32).…”
mentioning
confidence: 99%